Recent advances in g-C3N4-based photo-enzyme catalysts for degrading organic pollutants. Issue 2 (4th January 2023) - Gu, Yaohua; Li, Siao; Li, Mingming; Wang, Xinyu; Liu, Ying; Shi, Keren; Bai, Xiaoyan; Yao, Qing; Wu, Zhiqiang; Yao, Huiqin
Abstract : In recent years, photocatalytic reactions have shown great potential in degrading organic pollutants because of their simple operation and no secondary pollution. Abstract : In recent years, photocatalytic reactions have shown great potential in degrading organic pollutants because of their simple operation and no secondary pollution. Graphitic carbon nitride (g-C3 N4 ) is one of the most frequently used photocatalyst materials in the field of photocatalysis because it is a form of photocatalytic material with facile synthesis, no metal, visible light response, and strong stability. Enzyme-catalyzed degradation has received extensive attention due to its broad selectivity, high efficiency, and environmental friendliness. Horseradish peroxidase (HRP), one of several oxidoreductases utilized for pollutant degradation, has a wide range of applications due to its mild reaction conditions and high stability. Exploring efficient platforms for immobilizing g-C3 N4 and HRP to develop photo-enzyme-coupled catalysis is an attractive practical topic. The coupling effect of g-C3 N4 and HRP improves the carrier separation efficiency and generates more active species, which finally realize the solar-driven non-selective destruction of organic pollutants. We describe the alteration of g-C3 N4 and the immobilization of HRP in detail in this study, and we outline recent developments in the photo-enzyme coupling of g-C3 N4 and HRP.